Quasi-Experimental Evidence on the Drivers of Index-Based Livestock Insurance Demand in Southern Ethiopia - Takahashi, Kazushi; Ikegami, Munenobu; Sheahan, M.; Barrett, Christopher B. (2014)
Microinsurance is widely considered an important tool for sustainable poverty reduction, especially in the face of increasing climate risk. Although index based microinsurance, which should be free from the classical incentive problems, has attracted considerable attention, uptake rates have generally been weak in low-income rural communities. We explore the purchase patterns of index-based livestock insurance in southern Ethiopia, focusing in particular on the role of accurate product comprehension and price, icluding the prospective impact of temporary discount coupons on subsequent period demand due to price anchoring effects. We find that randomly distributed learning kits contribute to improving subjects' knowledge of the products; however, we do not find strong evidence that the improved knowledge per se induces greater uptake. We also find that reduced price due to randomly distributed discount coupons has an immediate, positive impact on uptake, without dampening subsequent period demand due to reference-dependence associated with price anchoring affects.